Perampanel and Challenging Behaviour in Intellectual Disability and Epilepsy: A Management Dilemma - Dolton, Emily; Choudry, Ansar (Case Reports in Psychiatry, 2014)
We describe a case of a patient with a diagnosis of moderate learning disability with challenging behaviour and treatment refractory epilepsy. Antiepileptics can increase challenging behaviour; however, antipsychotics can provoke seizures. This results in a difficult balance for patient care. Due to worsening seizures, the patient was prescribed perampanel. This increased her aggression and agitation resulting in admission. We trialled four antipsychotic drugs to reduce her challenging behaviour, two of which worsened her seizures. It was necessary to continue antiepileptic medication to maintain adequate seizure control. However, the resulting uncontrolled challenging behaviour persisted, meaning she was unable to return to her family home on discharge. This case emphasises the difficult scenario clinician’s encounter when balancing the use of antipsychotics and antiepileptics. The case demonstrates the significant functional loss due to challenging behaviour, balanced against controlling life threatening seizures.